Implementation Of Digital Application-Based Education On The Dangers Of Smoking On The Smoking Attitudes And Behavior Of Grade 6 Students Of Sdn Cerme 1 - Intan Fazrin; Muhammad Miftachul Mafakhir; Zainal Andy Saputra; Ridha Rachmathiany (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Smoking is the activity of burning tobacco wrapped in nipah leaves or paper, then inhaling and exhaling the smoke. Smoking is a habit that can damage the health of the body, both for active and passive smokers. In an effort to increase knowledge about the dangers of smoking, education can be done through digital application media. Sutori is one of the digital applications that has features that support use in educational activities. This study aims to determine the effect of education with digital application media on smoking attitudes and behavior in grade 6 students of SDN Cerme 1. This type of research is quantitative using pre-experimental with a one group pre-test post-test design approach with a total sampling method of 49 respondents. This study was conducted on June 8, 2024 using a questionnaire. Data analysis using the Wilcoxon test with a Z-Score result of -6.095 and an asymp value. Sig 2-tailed 0.000 which concluded that H0 was rejected and H1 was accepted which means that there is an influence of providing education with digital application media on the smoking attitudes and behavior of grade 6 students of SDN Cerme 1. Education through application media is one of the effective ways to provide knowledge. Complete and interesting features can make learning more interesting and not boring So that someone fully understands the concept presented to improve their cognitive abilities.